AN ANALYSIS OF LEARNER LANGUAGE IN INDONESIAN-ENGLISH TRANSLATION OF ENGLISH EDUCATIONAL STUDY PROGRAM STUDENTS OF UNIVERSITAS NAHDLATUL ULAMA LAMPUNG - Ruri Supatmi; Desy Awal Mar’an (LET: Linguistics, Literature and English Teaching Journal, 2021)
Translation becomes so important since it is the process of replacing the source language into the target language without replacing the intended meaning. The learners usually bring their previous competence of language on performing the second language. The communication process either spoken or written is the way to interpret the other people’s language even in different culture or language. Thus, the purpose of the source language in the text delivered accurately.This research was aimed at describing learner languages phenomena related to the five procedures of translation then showing the precentage of learner language in translation procedures from Indonesian to English.The data collecting methods used interview and documentation. The data was gathered from the students’ result of translation 2 semester test at Universitas Nahdlatul Ulama Lampung. The research was conducted toward thirty three of the sixth semester students of English Educational Study Program of Universitas Nahdlatul Ulama Lampung .the result of the research showed that most of the students’ learner languages and errors were found in translation procedures, the highest percentage of learner language in translation procedure in Indonesian-english translation was transposition, and the students didn’t understand about translation procedures.